Terahertz and mid infrared radiation generation, detection and applications - Shulika, Oleksiy (NATO Science for Peace and Security Series B: Physics and Biophysics, 2011)
Terahertz (THz) and Mid-Infrared (MIR) radiation (TERA-MIR) can be transmitted through nearly any material without causing biological harm. Novel and rapid methods of detection can be created with devices operation in these spectral ranges allowing scanning for weapons, detecting hidden explosives (including plastic landmines), controlling the quality of food and a host of other exciting applications. This book focuses on mathematical and physical aspects of the field, on unifying these two spectral domains (THz and MIR) with regard to common sources, detectors, materials and applications, and on key interdisciplinary topics. The main THz and MIR source is the quantum cascade laser (QCL). Thus significant attention is paid to the challenge of turning this advanced technology into affordable commercial devices so as to exploit its enormous potential. However other alternatives to THz QCLs are also presented, e.g. sub-terahertz imaging from avalanching GaAs bipolar transistors, Josephson junctions as THz sources, semiconductor materials for pulsed THz sources, superconducting THz electronics with Josephson vortices. In summary this book delivers a global picture of the state of the art in TERA-MIR generation, detection and applications.